Adult vaccination against respiratory infections in Egypt: a review of expert opinions - Ashraf Madkour; Adel M. Elsayed; Hala Sweed; Ibrahim El Ebrashy; Magdy Abdelhamid; Mohamed Zidan (Expert Review of Vaccines, 2024)
Introduction Lower respiratory tract infection is one of the leading causes of morbidity and mortality all over the world, with a substantial impact on healthcare costs. In Egypt, local consensus on its burden, diagnosis, and vaccination is scarce. This expert opinion is the first to address the local recommendations for vaccinating adults against respiratory infection. It sheds light on the growing need to understand the barriers and underpublicized concept of adult vaccination in Egypt.Areas covered A collaborative multidisciplinary panel from Egypt developed an expert opinion-based suggestions/points, including epidemiology, microbiology, and highlights on vaccination in Egypt, as well as challenges and recommendations regarding adult vaccination.Expert opinion Adult vaccinations against respiratory infections are now recommended for high-risk people by all healthcare regulatory bodies. However, it was acknowledged that there may be hesitancy and concerns among patients; in addition, healthcare professionals’ awareness about vaccination guidelines and benefits needs improvement. There are several strategies that could be implemented to enhance vaccine adherence in Egypt. These approaches encompass conducting community education programs, addressing the concerns of patients, and enhancing awareness among healthcare professionals through education, policy changes, and periodical reminders in each healthcare setting.